2022
DOI: 10.1038/s41598-022-04794-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of impaired renal allograft function in paediatric and young adult patients using arterial spin labelling MRI (ASL-MRI)

Abstract: The study aimed to discriminate renal allografts with impaired function by measuring cortical renal blood flow (cRBF) using magnetic resonance imaging arterial spin labelling (ASL-MRI) in paediatric and young adult patients. We included 18 subjects and performed ASL-MRI on 1.5 T MRI to calculate cRBF on parameter maps. cRBF was correlated to calculated glomerular filtration rate (GFR) and compared between patient groups with good (GFR ≥ 60 mL/min/1.73 m2) and impaired allograft function (GFR < 60 mL/min/1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The occurrence of AR in kidney transplantation has been significantly reduced; however, with an AR rate of less than 10% in the first year after kidney transplantation, AR episodes still dramatically affect graft survival ( 14 , 41 43 ). Therefore, prompt identification and intervention for AR are vital for improving graft outcomes ( 44 ). Here, we performed the RNA-seq to analyze the DEGs in the peripheral blood of AR recipients collected before renal transplantation and at the time of AR episode to acquire the expression changes of DEGs from pre-operation to the AR episodes.…”
mentioning
confidence: 99%
“…The occurrence of AR in kidney transplantation has been significantly reduced; however, with an AR rate of less than 10% in the first year after kidney transplantation, AR episodes still dramatically affect graft survival ( 14 , 41 43 ). Therefore, prompt identification and intervention for AR are vital for improving graft outcomes ( 44 ). Here, we performed the RNA-seq to analyze the DEGs in the peripheral blood of AR recipients collected before renal transplantation and at the time of AR episode to acquire the expression changes of DEGs from pre-operation to the AR episodes.…”
mentioning
confidence: 99%
“…Accordingly, the diffusion of water molecules was restricted and deviation from the Gaussian distribution became more serious. The glomerular filtration is susceptible to the blood perfusion, and the reduction of blood supply principally occurred in cortex rather than medulla considering around 90% of renal blood flow generally exists in cortical microvessels [ 30 ]. This may explain why the mean value of D in cortex have achieved the strongest correlation with eGFR in our study, which was consistent with the result that shown in the study of Mao et al [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, ASL perfusion MRI with endogenous water molecules as a tracer alleviates such complicated and uncertain agent-tissue interaction problems. In the situation in which the concern over the clearance and safety of the Gd-based contrast agents, 78 such as patients with abnormal renal functions, ASL perfusion MRI provides an excellent alternative if motion artifacts and acquisition time with the spin-label scheme designed for the flow and magnetic properties of water in the blood are manageable by the performance of the gradient and RF systems of the MRI scanners and blood flow kinetics in the vasculature of the organs, such as brain 79 and kidney, 80 where ASL perfusion MRI has been used with examples shown in Figure 7 . More importantly, because the measurement of the amount of endogenous water flowing into the tissue is affected by the concentration-dependent change of contrast or signal intensity in the DSC MRI, the regional cerebral blood flow (rCBF) rate and regional cerebral blood volume (rCBV), when used in a brain, can be calculated accurately.…”
Section: Molecular and Functional Imaging Using Water Molecules As Pr...mentioning
confidence: 99%
“…T 2 weighted image was used to place the slice (red line) where the labeling RF was applied. Reprinted with permission from ref ( 80 ). Copyright 2022 Springer Nature.…”
Section: Molecular and Functional Imaging Using Water Molecules As Pr...mentioning
confidence: 99%